53 Evaluation of nutrient digestibility, apparent absorption and retention of zinc in lambs supplemented with zinc from zinc hydroxychloride, zinc sulfate or zinc methionine. - VanValin, K (J Anim Sci, 2018)
This study sought to determine if Zn supplementation from Zn hydroxychloride would increase Zn retention and nutrient digestibility compared to lambs supplemented with Zn methionine, Zn sulfate (ZnSO(4)), or no supplemental Zn. Thirty-six crossbred poly-pay wethers (initial BW 31.5 ± 3.56 kg) were stagger started on a common depletion diet (22 mg Zn/kg DM) for 52 d (3 groups of 12 lambs). Day 52 BW (43.2 ± 3.28 kg) were used to block to dietary treatments: CON: depletion period diet with no supplemental Zn; ING: CON + 40 mg Zn/d from ZnSO(4); ORG: CON + 40 mg Zn/d from Zn methionine; HYD: CON + 40 mg Zn/d from Zn hydroxychloride. Zinc treatments were top dressed daily with fine ground corn. On d 53 lambs were placed in metabolism crates and dietary treatments started for a 10 d adaptation period followed by 5 days of total fecal and urine collection. Dry matter intake (kg/d) was similar (P≥0.41) for CON (1.21), ING (1.23), ORG (1.19), and HYD (1.18). Zinc apparent absorption was greater (P < 0.001) in CON lambs fed only the Zn depletion diet (22.7%) than in lambs receiving supplemental Zn: ING (10.3%), ORG (10.9%), and HYD (11.4%). This resulted in Zn retained (mg/d) being similar (P ≥ 0.58) for CON (5.92), ING (6.72), ORG (6.88), and HYD (7.21). Dry matter digestibility was lesser for ORG compared to HYD (70.1 vs. 72.0%; P = 0.05) as was NDF digestibility (40.6 vs. 45.0%; P = 0.05) while ING did not differ from HYD (P ≥ 0.29). Zinc retention was similar for lambs regardless of dietary Zn concentration or source, suggesting lambs of this size have a Zn requirement of 6–7 mg/d which may have precluded source differences. The data also suggest that supplemental Zn source may impact nutrient digestibility.